Community Satisfaction Survey of Loa Ipuh Health Center 2024–2025 Based on Ministerial Regulation No. 14/2017 - Reza Jales Mahesa Adiyatsa; Ratno Adrianto (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The Community Satisfaction Survey is an essential instrument for evaluating the quality of public services as mandated by the Indonesian Ministry of Administrative and Bureaucratic Reform Regulation No. 14 of 2017. This instrument assesses users’ perceptions of service quality based on nine service elements. In the health sector, this survey serves not only as a measurement tool but also as a foundation for continuous quality improvement. Objective : This study aims to compare the service performance of Loa Ipuh Health Center in 2024 and 2025 using a descriptive analysis approach based on primary survey data involving 375 respondents in each year. Research Methods/ Implementation Methods : The evaluation covers all nine service elements and performance across service units (poli) following the guidelines of the Community Satisfaction Index (IKM). Results : The results show an increase in IKM from 87.06 in 2024 to 87.50 in 2025, indicating an overall improvement in service quality, although the increase remains modest. The highest-scoring elements in both years were Staff Attitude and Service Fees/Tariffs, reflecting positive public perceptions of staff behavior and cost affordability. Conversely, Service Specifications and Service Timeliness were the lowest-scoring elements, suggesting challenges related to service consistency and waiting time. Analysis across service units also revealed performance variations, with the KIA, Nutrition, and Procedure Units performing well, while the Laboratory and Registration Units scored below average. Conclusion/Lesson Learned : These findings highlight the need for targeted improvements in weaker elements and units to strengthen overall service quality in subsequent years.